Design and Development of an MQ-2 Sensor and Arduino Uno Gas Leak Detection System with Automatic Ventilation and Warning - Uvi Desi Fatmawati; Dananjaya Ariateja; , Satria Putra Akbar; Muhammad Nizar Helmy Roesdian; Grujs Ramadhan Raihan Rafif; Mulayasa Sparta Kusuma; Raul Gonjales Barus (Jurnal Penelitian, 2026)
Gas leakage can create fire, explosion, and health hazards when it is not detected promptly. This study developed a laboratory-scale gas-leak detection prototype that integrates an MQ-2 metal-oxide sensor, Arduino Uno, 16×2 I2C LCD, audible and visual warnings, a relay, and an automatically activated exhaust fan. Prototype performance was evaluated through distance-based sensor-response tests, alarm-response-time trials, and time-resolved ventilation tests. The average MQ-2 output declined from 721.0 ADC counts at 5 cm to 150.0 ADC counts at 30 cm, indicating a consistent distance-dependent response under the reported test conditions. The warning chain activated in an average of 2.0 s. After fan activation, the average ADC response decreased by 46.7% after 30 s and 79.9% after 60 s relative to the initial reading. These percentages describe changes in relative sensor output, not calibrated gas concentration, because no certified reference-gas or parts-per-million calibration was performed. The prototype demonstrates the feasibility of combining local detection, warning logic, and automatic ventilation in one low-cost platform. It is intended as an educational and supervised proof of concept and should not be treated as a substitute for a certified combustible-gas detector or explosion-protected safety system.